2017
DOI: 10.1007/s10951-017-0513-5
|View full text |Cite
|
Sign up to set email alerts
|

Solving a wind turbine maintenance scheduling problem

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Within a work shift, various tasks must be completed on a wind turbine according to the prevailing time and labour force restrictions. As stated in [11], it is almost impossible to generate a flawless maintenance plan in terms of avoiding production loss, since it is difficult to find a period where the turbine is not producing due to low wind speeds. What can be done in this sense is to schedule the maintenance with an acceptable uncertainty [27,28].…”
Section: Maintenance Plans and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Within a work shift, various tasks must be completed on a wind turbine according to the prevailing time and labour force restrictions. As stated in [11], it is almost impossible to generate a flawless maintenance plan in terms of avoiding production loss, since it is difficult to find a period where the turbine is not producing due to low wind speeds. What can be done in this sense is to schedule the maintenance with an acceptable uncertainty [27,28].…”
Section: Maintenance Plans and Problem Statementmentioning
confidence: 99%
“…In other words, finding an appropriate weather window is a major criterion for any type of intervention for wind turbines and there is a research need closing the gap between academic models and application in practice [10]. According to the literature, maintenance weather windows are dependent on the wind speed for an onshore wind farm, while the wave height is also a decisive factor for offshore wind farms where accessibility depends on the type of maintenance vessel utilized [11][12][13][14]. For offshore wind farm operations, the location (distance to shore and water depth), meteorological and oceanographic variables influence the site accessibility, it is highlighted in the literature that there is a trend of moving from near-shore to deep water for offshore wind farm installations, which results in lower site accessibility and higher costs for the executions of corrective maintenance actions [15].…”
Section: Introductionmentioning
confidence: 99%
“…We consider the wind turbine maintenance scheduling problem, focusing on onshore wind farms, introduced by Froger et al (2017). The problem is to provide a maintenance plan over a short-term horizon that maximizes wind electricity production while taking into account fine-grained resource management involving task assignments to a multi-skilled workforce.…”
Section: Introductionmentioning
confidence: 99%
“…The problem is to provide a maintenance plan over a short-term horizon that maximizes wind electricity production while taking into account fine-grained resource management involving task assignments to a multi-skilled workforce. Froger et al (2017) introduced several models based on ILP and constraint programming (CP). They found that the computational time grows prohibitively with problem size, and they therefore proposed a CP-based large neighborhood search (CPLNS) approach.…”
Section: Introductionmentioning
confidence: 99%
“…This can be done if wind power turbines operate efficiently at broader wind speed ranges, while maintaining optimum electrical generator shaft speeds, so they can generate more electric power regardless of the wind speed. There is a great impact on the turbine reliability when major components of the wind power turbine like the gearbox or the generator fail because this creates an extended mean time to repair (MTTR) [4][5][6]. Therefore, reducing failure and maintenance of these major components reduces the cost of operation of the wind power turbine, which in turn reduces the cost of energy itself.…”
Section: Introductionmentioning
confidence: 99%